IRRIGATION AND FERTIGATION FOR SUBSUPERFICIAL AND SUPERFICIAL DRIP IN BROCCOLI CROP - Reis, Karoline Maso Dos; Palaretti, Luiz Fabiano [UNESP]; Barreto, Antônio Carlos; Zanini, José Renato [UNESP] (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2021)
The use of irrigation increases yields and protects crops from the seasonality of precipitation; however, its application must be based on technical and operational criteria. This work aimed to evaluate the hydraulic performance of drip emitters and the development of the broccoli crop submitted to drip irrigation on surface and subsurface, with and without fertigation. The experiment was designed in randomized blocks (RBD), with four replications. The treatments were constituted of the positions of drip emitter at depths of 0.00; 0.10 and 0.20 m; and the application of fertilizers, that was made by fertigation and manual fertilizing. In relation to drip emitter, flow, flow variation coefficient (Cv), Christiansen uniformity coefficient (CU), distribution uniformity coefficient (DU) and degree of clogging of the emitter (Ec) were evaluated; regarding the crop response, the diameter of the flower stalk, the diameter of the inflorescence, the diameter of the inflorescence (perpendicular), height of the inflorescence, fresh mass of the inflorescence, days of transplantation until harvest and water productivity was analyzed. There were no significant changes in the characteristics evaluated of the drip emitter and in the production of broccoli crop in terms of the depth of the emitter and the way of application of the fertilizers.
IRRIGAÇÃO POR GOTEJAMENTO SUBSUPERFICIAL E FERTIRRIGAÇÃO DA CULTURA BRÓCOLIS
Keywords: Brassica oleracea var. itálica; localized irrigation; water productivity